PERNIKAHAN DINI DAN AGENDA KEBIJAKAN KE DEPAN (KASUS DI KABUPATEN SLEMAN) - Muhammad Arif Fahrudin Alfana; Beti Nur Hayati (Yogyakarta State University, 2017)
This study has two main objectives. The first is to explain the condition of early marriage that occurred in Sleman District. Second, is to explain the agenda of population policy in the future to overcome the problems of early marriage that occurred. The data used is the marriage data of children in Sleman District in 2012-2015. The data is sourced from the Department of Population and Civil Registry and the Office of Religious Affairs of Sleman Regency. Data analysis was done by descriptive analysis. The results showed the number of early marriages is high. Every year, in 2013-2015, more than 100 cases of early marriage occur in Sleman. Early marriage also spread evenly across districts in Sleman District. Of all the existing sub-districts, Mlati and Ngaglik sub-districts are subdistricts that naturally or absolute have marriage cases in Sleman District. That's why some policy agenda is prepared to address the problem of early marriage. Some of these policy agendas include raising the median age of women's first marriage, lowering ASFR 15-19 and increasing enrollment rates at senior high scholl by 91.63% in 2019.Keyword: Early Marriage, Population Policy, and Sleman District